Emerging Roles of Myeloid-Derived Suppressor Cells in Diabetes - Wang, Shiqi; Tan, Qian; Hou, Yayi; Dou, Huan (Frontiers in Pharmacology, 2021)
Diabetes is a syndrome characterized by hyperglycemia with or without insulin resistance. Its etiology is attributed to the combined action of genes, environment and immune cells. Myeloid-derived suppressor cell (MDSC) is a heterogeneous population of immature cells with immunosuppressive ability. In recent years, different studies have debated the quantity, activity changes and roles of MDSC in the diabetic microenvironment. However, the emerging roles of MDSC have not been fully documented with regard to their interactions with diabetes. Here, the manifestations of MDSC and their subsets are reviewed with regard to the incidence of diabetes and diabetic complications. The possible drugs targeting MDSC are discussed with regard to their potential of treating diabetes. We believe that understanding MDSC will offer opportunities to explain pathological characteristics of different diabetes. MDSC also will be used for personalized immunotherapy of diabetes.